Role of Ca, Fe, Cu and Zn in breast cancer: Study by X-ray fluorescence techniques and immunohistochemical analysis - Silva, Márcio Pereira da [UNESP]; Silva, D. M.; Conceição, A. L C; Ribeiro-Silva, A.; Poletti, M. E. (Wiley, 2013)
In recent years, several studies have shown that concentrations of trace elements are altered in neoplastic breast tissues. However, the microenvironment and metabolic changes caused by tumors are complex and still not completely understood. Under this aspect, the combination of different techniques to investigate the role of trace elements in promoting and/or maintaining a tumor is interesting once the combination of information obtained by analytical techniques and immunohistochemical assays, associated with clinicopathological data, may allow a better metabolic understanding of trace elements in breast cancer. In this work, the role of the trace elements Ca, Fe, Cu and Zn in neoplastic breast tissues was investigated by X-ray fluorescence (XRF) techniques and immunohistochemical assays. We determined concentrations of Ca, Fe, Cu and Zn in normal and neoplastic breast tissues using energy dispersive XRF, and these values were used to set the positive or negative expression of elements in normal and neoplastic tissues. These expressions were correlated with the spatial distributions of trace elements (evaluated by micro-XRF) and with immunoexpression of matrix metalloproteinases (MMPs), tissue inhibitors of MMPs and vascular endothelial growth factor. The results revealed that the expression of the trace elements Fe, Cu and vascular endothelial growth factor are related, indicating that higher levels of these elements can be associated with the angiogenic process in breast cancer. Also, associations between Ca, Zn and MMPs expression have been observed, possibly because of the fact that both metals are present in these proteins. © 2013 John Wiley & Sons, Ltd.